2021
DOI: 10.48550/arxiv.2106.05268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vector Symbolic Architectures as a Computing Framework for Nanoscale Hardware

Abstract: This article reviews recent progress in the development of the computing framework Vector Symbolic Architectures (also known as Hyperdimensional Computing). This framework is well suited for implementation in stochastic, nanoscale hardware and it naturally expresses the types of cognitive operations required for Artificial Intelligence (AI). We demonstrate in this article that the ring-like algebraic structure of Vector Symbolic Architectures offers simple but powerful operations on highdimensional vectors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…In this work, we enhance the machine learning method by exploring and translating the memory processing capability of the brain [40]. To maximize the synergy between anthropogenic concepts and a body in silico, we analyzed the distinct neuromorphic nature of SNN and Vector Symbolic Architecture (VSA) [44,45]. We found that the two studies approach neuromorphic computing from complementary philosophies: SNN embodies the sensory processing patterns of the brain from a biological standpoint, while the VSA approach processes data from the behavioral patterns.…”
Section: Analogy From the Brainmentioning
confidence: 99%
“…In this work, we enhance the machine learning method by exploring and translating the memory processing capability of the brain [40]. To maximize the synergy between anthropogenic concepts and a body in silico, we analyzed the distinct neuromorphic nature of SNN and Vector Symbolic Architecture (VSA) [44,45]. We found that the two studies approach neuromorphic computing from complementary philosophies: SNN embodies the sensory processing patterns of the brain from a biological standpoint, while the VSA approach processes data from the behavioral patterns.…”
Section: Analogy From the Brainmentioning
confidence: 99%
“…Examples of the new paradigms are neuromorphic and nanoscalable computing, where HDC/VSA is prospected to play an important role (see [Kleyko et al, 2021a] and references therein for perspective). Due to this surge of interest in HDC/VSA, the need for providing the broad coverage of the area, which is currently missing, became evident.…”
Section: Introductionmentioning
confidence: 99%
“…cognitive architectures [Plate, 1997a] ± ± [Kanerva, 2009] ± ± ± ± ± [Neubert et al, 2019] ± ± ± ± [Ge and Parhi, 2020] [ Schlegel et al, 2020] ± ± ± [Kleyko et al, 2021a] ± [Hassan et al, 2021…”
mentioning
confidence: 99%
“…In classification tasks, the use of VSA leads to order of magnitude increase in energy efficiency of computations on the one hand and natively enables oneshot and multitask learning on the other [7]. It is prospected that VSA will play a key role in the development of novel neuromorphic computer architectures [8] as an algorithmic abstraction [9], [10]. The main contribution of this paper is a novel algorithm for unsupervised learning called Hyperseed, which relies on the mathematical properties of arising from random representation spaces described through the concentration of measure [11] and of the main VSA operations of binding and bundling [12].…”
Section: Introductionmentioning
confidence: 99%